Unusual finding during laparoscopic cholecystectomy: liver choristoma in the gallbladder wall - Echeverry-Gutiérrez, Miguel Ángel; Muñoz Mata, Karla Paola; Zavala-Perez, Jose Manuel; Reyes-Gonzalez, Saul Ernesto; Trejo-Gonzalez, Marco Antonio (International Journal of Research in Medical Sciences, 2024)
Hepatic choristomas or ectopic livers are rare developmental anomalies and are usually located in the abdomen, retroperitoneum and thorax. A 34-year-old male patient underwent a scheduled laparoscopic cholecystectomy, the findings during surgery were a gallbladder with multiple lithiasis inside, with a smooth fragment of reddish-brown tissue attached to the anterolateral surface of the gallbladder. The patient evolved satisfactorily and was discharged 24 hours after surgery. Objective was to describe a clinical case of hepatic choristoma adhered to the anterolateral wall of the gallbladder, as well as its etiology, clinical picture and therapeutic conduct. Hepatic choristoma in the gallbladder is due to an anomaly in the embryologic development of the liver, due to its potential for malignant degeneration, it should be resected as soon as it is detected, being laparoscopic cholecystectomy an adequate approach.